Lipopolysaccharide exacerbates infarct size and results in worsened post-stroke behavioral outcomes. Issue 1 (December 2015) - Doll, Danielle; Engler-Chiurazzi, Elizabeth; Lewis, Sara; Hu, Heng; Kerr, Ashley; Ren, Xuefang; Simpkins, James
Abstract Background A third of ischemic stroke cases have no traditional underlying causes such as hypertension, diabetes, atherosclerosis, obesity, or age. Moreover, thirty to forty percent of strokes occur during or acutely after an active infection and the incidence of stroke increases during flu season. We and others have shown that the combination of a minor bacterial infection mimic, 100 μg/kg of lipopolysaccharide (LPS) prior to a minor stroke—30 min transient middle cerebral artery occlusion (tMCAO)—exacerbates infarct volume in a mouse model. Thus, experimental and epidemiological data strongly suggest that infection and/or inflammation play a role in stroke occurrence and severity. However, to date, long-term outcomes of stroke during an active infection has not been studied. Methods 3–4 month old C57Bl6/J mice were treated with saline or LPS 30 min prior to a 30 min tMCAO or sham surgery. A behavioral battery was administered to assess health status/sickness behavior, neurological deficits, motor, cognitive, and affective behaviors. Results We show for the first time that exposure to a low dose of LPS prior to a mild stroke significantly worsens neurological deficits and sickness scores. Motor, cognitive, and affective behaviors were assessed post-stroke and while stroke significantly affected motor behavior on rotarod, LPS did not increase the motor deficits. We did not observe any effects of stroke or LPS on cognitive and affective behaviors. Conclusions Our observations of the association between infection, stroke, and worse sickness and neurological outcomes identify (1) a clinical need to aggressively treat infections in people with risk factors for stroke and (2) the need to understand the mechanism(s) of the association between infections and stroke.